Athletes’ Perception of Basic Pencak Silat Book at the White Eagle College of North Musi Rawas Regency - Sinaga, Victor; Lanos, Muhsana El Cintami; Handayani, Widya (Journal of Social Work and Science Education, 2023)
This study aims to determine athletes’ perceptions of the use of basic pencak silat motion books, (1) athletes’ perceptions of pencak silat training, (2) the use of media in pencak silat training, (3) the need for the development of pencak silat books. This research is descriptive quantitative research. The results of this study stated that (1) Athletes’ perception of pencak silat training obtained a value of 75.81%, with a good category (2) The use of media in training obtained a value of 85%, very good (3) the need for the development of pencak silat books amounted to a value of 93.25% with the category of strongly agree. The results of this study show that athletes’ perceptions of the development of pencak silat books in the white eagle college of North Musi Rawas Regency are positive, for that it is necessary to develop pencak silat books in the white eagle college of North Musi Rawas Regency.